Clinical and subclinical manifestations and causes of diabetes insipidus at Bach Mai Hospital (2013-2017) - Van, Nguyen Khoa Dieu; Huong, Nguyen Thi (Vietnam Journal of Diabetes and Endocrinology, 2023)
Background: In Vietnam, there are no specific studies on subclinical and clinical manifestationsand causes of diabetes insipidus in adults. Study objectives:1. To evaluate the subclinical and clinical manifestations of patients with diabetes insipidus treated at the Department of Endocrinology and Diabetes at Bach Mai Hospital. 2. Comments on some causes of diabetes insipidus in the study sample. Materials and methods: 1.Object: 120 patients with diabetes insipidus treated at Bach Mai Hospital. 2.Methods: Descriptive cross-sectional study, retrospective and prospective. Results: Incidence of diabetes insipidusamong men and women is the same, with average age of 38.50 ± 14.28. Common clinical symptoms are heavy drinking of water, polyuria, thirst, and nocturia (>80%). Average output of urine is 5.67 ± 5.00 liters/day, the amount of water drunk is 5.30 ± 2.23 liters/day. Pituitary dysfunction is 30 to 45%.Average of urine specific gravity is 1,007 ± 0,005. Average of urine osmolality is 208,14 ± 136,99 m0smol/kg. 3/120 patiens have disorder of consciousness, 27,5% have sodium blood level higher than 145 mmol/l. 115/120 patients have central diabetes insipidus, in which brain surgery accounts for 48,7%, tumor brain accounts for 26,9%, unknown is 20,9%, traumatic brain injury is 3,5%. Nephrogenic diabetes insipidus has3,4%. Diabetes insipidus in pregnancy happens to 1 patient. Conclusion: Cause of diabetes insipidus is mostly central, mainly after pituitary surgery. About 40% of the patients have hypopituitarism. Some other reasons to consider such as nephrogenic diabetes insipidus (inherited or acquired), diabetes insipidus in pregnancy.